CONTRIBUTION OF SCHOOL TO DEVIANT BEHAVIORS AMONG STUDENTS IN SECONDARY SCHOOLS: A CASE OF TRANS-NZOIA WEST SUB-COUNTY, KENYA - Mideva, Mugami Margaret (IJRDO- Journal of Educational Research, 2018)
Deviant behaviors among secondary school going populations, the world over, are of concern to educators, counselors and psychologists. This is because of the potential of deviant behaviors at the adolescent stage to undermine the achievement of both personal and national goals. Your social environment including your family, friends, school, and neighborhood influence your behavior. This study assessed the contribution of social institution (school) to deviant behaviors among secondary school students. The study was anchored on the Social-control Theory by Travis (1960) and Attachment Theory by Bowlby and Ainsworth (1991). Descriptive survey design was used because the deputy head teachers’ guidance and counseling teachers’ and students’ attitudes were sought. The target population was 6529 respondents. The sample size was 661 respondents. Simple Random Sampling was used to select the schools and the students. Stratified Sampling was used to select the zones then Purposive Sampling was used to select deputy principals and guidance and counseling teachers. The researcher used questionnaires and behavior assessment tool as the instruments to collect qualitative and quantitative data necessary for this study. The study was carried out in Trans-Nzoia West Sub-County. Reliability was established by test-retest method in a pilot study done in the neighboring sub-county. Validity was established by giving the instruments to the experts in research field. Content validity was adopted for this study. Descriptive techniques of data analysis such as frequencies, percentages, means and standard deviations were used. To establish the relationship, Spearman’s rank was employed while t-test was used to test for significance. The data was subjected to Statistical Package for Social Sciences version 17 for further analysis. The study revealed the following: that the frequency of deviance in schools is low in the study area, secondly the school contributes to deviant behaviors among students by having aggressive peers, peer pressure, lack of a culture of learning and overloaded curriculum. The study recommended that the Ministry of Education should ensure that each school has a counseling room and all guidance and counseling teachers should be exposed to workshops and seminars to enable them be effective in their work.